Peningkatan kualitas pembelajaran prakarya dan kewirausahaan melalui metode CLTSMK - Galeh Nur Indriatno Putra Pratama; Moch. Bruri Triyono (Jurnal Pendidikan Vokasi, 2015)
Penelitian ini bertujuan untuk mengungkapkan: (1) peningkatan sikap belajar siswa dan (2) proses peningkatan kompetensi dasar mengidentifikasi sumber daya dan membuat desain karya rekayasa dengan penggunaan metode pembelajaran CLTSMK pada mata pelajaran Prakarya dan Kewirausahaan yang ditunjukkan melalui motivasi, kreativitas, dan kemampuan manajerial siswa kelas X Kimia Industri di SMKN 2 Depok. Penelitian ini merupakan PTK, mengacu pada model Kemmis & Mc. Taggart. Penelitian terdiri atas siklus I-III melalui tahapan perencanaan, tindakan, pengamatan, dan refleksi. Subjek penelitian 32 siswa, kelas X Kimia Industri. Pengumpulan data menggunakan lembar observasi dan wawancara. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan: (1) persentase rerata peningkatan siklus I-III sebesar 41,611%, 36,053%, dan 9,551% tinjauan motivasi; 29,239%, 40,458%, dan 18,231% tinjauan kreativitas; 30,774%, 32,311%, dan 16,996% tinjauan kemampuan manajerial siswa dan (2) proses upaya peningkatan sikap belajar melalui motivasi, kreativitas, dan kemampuan manajerial siswa terdiri atas empat fase. THE IMPROVEMENT OF THE QUALITY OF CRAFT AND ENTREPRENEURSHIP TEACHING THROUGH CLTSMK METHODAbstractThis research aims to reveal: (1) the improvement of the learning attitude and (2) the process to the improvement of basic competencies in identifying resources and create an engineering work design by using CLTSMK learning method in Craft and Entrepreneurship subject shown by motivation, creativity, and managerial ability in Chemical Industry of class X students of SMKN 2 Depok. This research is classroom action research, design refers by Kemmis & Mc. Taggart. This research consisted of cycle I-III, the stages of research consist of planning, action, observation, and reflection. The subject of this research was 32 class X students of Chemical Industry. The data were collected using observation and interview guides. The data were analyzed using descriptive analysis techniques. This research results showed: (1) the mean percentage improvement of the condition of cycle I-III subsequently are 41.611%, 36.053%, and 9.551% for the observation of students' motivation; 29.239%, 40.458%, and 18.231% for the observation of students' creativity; 30.774%; 32.311%; and 16.996% for the observation of students' managerial ability and (2) the process of improving the students' learning through motivation, creativity, and managerial ability consists of four phases.